Beer, brains, and brawn as tools to describe terrestrial gastropod species richness on a montane landscape. Issue 12 (17th December 2018) - Lucid, Michael K.; Ehlers, Shannon; Robinson, Lacy; Cushman, Samuel A.
Abstract: Terrestrial gastropods are part of one of the most vulnerable taxonomic groups, mollusks, but receive relatively little conservation attention. This is partially due to the paucity of peer‐reviewed statistical evaluations of common survey techniques. From 2010 to 2014, we conducted a massive survey for terrestrial gastropods in a montane region centered on northern Idaho and including portions of northeastern Washington and northwestern Montana, USA. We fused several commonly used gastropod survey techniques (cover board traps baited with beer or water, pitfall traps, visual search, and leaf litter sorting) into a single survey transect which we deployed at 991 survey sites across our 22, 975‐km 2 study area. We used a variety of variables, including air temperature (collected at each site for ≥12 calendar months) and relative humidity to evaluate the effects of seasonality, observer bias, and repeated site visits on collection rate of individual specimens and detection of numbers of species. We found a combination of timed searches and leaf litter to be most effective in describing the maximum number of species with the least amount of effort. Although re‐visiting sites significantly increased the number of species detected, more time spent at each site likely would have a similar effect and preclude the need for additional expense to visit remote survey locations. Observer bias was determined not to be a factor of concern for within‐group observers. But when grouped by observer type, different classifications of observers performed quite differently. Beer, regardless of brand, was clearly a superior trap bait to water. However, because traps outperformed timed searches only slightly for one gastropod sub‐group (small slugs) we do not recommend trapping, beer baited or otherwise, be used as part of major landscape‐level survey efforts. Our study is the most extensive evaluation of survey techniques available in the literature to date and provides a framework for other practitioners implementing landscape‐level surveys for terrestrial gastropods.